Status Hukum Tanah Hasil Korupsi dalam Peralihan Hak dan Perlindungan Pembeli Beritikad Baik - Sudja'i; Moh. Bangkit Abdur Rohman (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
This study conducts a literature review on the civil law position of land derived from corruption, focusing on the validity of land rights transfer and the protection of good faith purchasers. Using qualitative methods with content analysis of legal texts and academic literature, the research reveals that the validity of land rights transfer cannot be determined monolithically but depends on the interaction between civil and criminal law provisions. From a civil law perspective, land transfer to purchasers meeting general sale requirements is valid, especially if they act in good faith. However, criminal law grants the state the right to trace and confiscate corruption-derived assets, which may limit such validity. The equilibrium point is found in the concept of good faith operationalized through objective due diligence standards. Purchasers meeting these standards through adequate examination, fair price payment, and proper transaction procedures deserve protection, rendering their land non-confiscable. Conversely, negligent or bad faith purchasers receive no protection, allowing state confiscation. The study identifies key indicators of good faith including price reasonableness, compliance with procedures, and purchaser awareness of red flags. It concludes that proportional protection balancing legal certainty in civil transactions with effective state asset recovery is essential for achieving justice in corruption asset handling.